Rola Ossolineum w pracy naukowej galicyjskiej inteligencji – na podstawie wspomnień i listów jego bibliotekarzy i czytelników - Chrostek, Mariusz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2024)
Zakład Narodowy im. Ossolińskich we Lwowie do roku 1918 to jedna z najważniejszych instytucji naukowych na ziemiach polskich pod zaborem austriackim. Przyczynili się do tego zasłużeni pracownicy, którzy oprócz typowych prac bibliotekarskich prowadzili badania naukowe. Byli wśród nich znani historycy i literaturoznawcy. O roli, jaką Ossolineum odgrywało w pracy naukowej przedstawicieli galicyjskiej inteligencji, świadczą ich wspomnienia i listy. Na ich podstawie poznajemy charakter i warunki pracy ossolińczyków, w tym współpracę korespondencyjną z szerokim gronem intelektualistów nie tylko z terenów dawnych ziem polskich, ale i z zagranicy.

Until 1918, the Ossolińskis National Institute in Lviv was one of the most important scientific institutions in the Polish lands under the Austrian partition. Distinguished employees also had their contribution: in addition to their typical library work, conducted scientific research. Among them were well-known historians and literary scholars. Their memoirs and letters testify to the role that Ossolineum played in the scientific work of representatives of the Galician intelligentsia. On their basis, we learn about the character and working conditions of the Ossolinians, including their cooperation by correspondence with a wide range of intellectuals, not only from the former Polish territories, but also from abroad.
The role of Ossolineum in the scientific work of the Galician intelligentsia – based on the memories and letters of its librarians and readers
Keywords: Ossolineum; Lwów; inteligencja w Galicji; pracownicy Ossolineum; naukowcy w Galicji; Lviv; intelligentsia in Galicia; Ossolineum employees; scholars in Galicia